1970
DOI: 10.1111/j.1432-1033.1970.tb01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Action Patterns of Phosphorylase and Glycogen Synthetase on Glycogen

Abstract: The action patterns of liver and muscle glycogen synthetases and of muscle phosphorylase b on glycogen samples of different molecular weight and on ,&amylase limit dextrins were studied. For this purpose a method for measuring the number of newly added glucose residues that are a t non-reducing ends was developed.It was found that glucose transfer to the non-reducing ends of glycogen catalyzed by liver glycogen synthetase and muscle phosphorylase followed a Poisson distribution.The number of outer chains in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…No close comparison can be made between this distribution and others (e.g. Parodi, 1967;Parodi et al, 1970) obtained with the method described by Mordoh et al (1966) because of the crudeness of calibration of the latter method. However, it is clear that these authors are assigning much higher molecular weights in comparison with the sedimentation coefficients which they calculated.…”
Section: Resultsmentioning
confidence: 58%
“…No close comparison can be made between this distribution and others (e.g. Parodi, 1967;Parodi et al, 1970) obtained with the method described by Mordoh et al (1966) because of the crudeness of calibration of the latter method. However, it is clear that these authors are assigning much higher molecular weights in comparison with the sedimentation coefficients which they calculated.…”
Section: Resultsmentioning
confidence: 58%
“…In studies on high molecular weight glycogen we detected some labile bonds, the rupture of which decreased the molecular weight from 3000 million to 8 million [15]. Perhaps those labile bonds correspond to the acid-labile glucan-protein bond described.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that GS is able to add several glucosyl residues successively to the same chain of a glycogen molecule, i.e. that elongation is processive . However, such a pattern of elongation is incompatible with a rapid equilibrium random mechanism, which predicts that exactly one glucose residue is successively incorporated in the same chain (distributive elongation) .…”
Section: Glycogen Synthase and Its Kineticsmentioning
confidence: 99%